Labor productivity, effort and the euro area business cycle - Vivien Lewis; Stefania Villa; Maik H. Wolters (Deutsche Bundesbank, 2019)
The Euro Area is characterized by little variation in unemployment and strongly procyclical labor productivity. We capture both characteristics in a New Keynesian business cycle model with labor search frictions, where labor can vary along three margins: employment, hours, and effort. We estimate the model with Bayesian methods and find evidence for a significant use of the effort margin in generating procyclical productivity. We show that a model with labor effort is more successful at matching the business cycle facts than is one with variable capital utilization or dominant technology shocks. Finally, we demonstrate that effort dampens the response of inflation to exogenous shocks.
Keywords: E30; E50; E60; 330; effort; labor utilization; labor productivity; inflation